“Há mister de saber que os subalternos também têm o direito de ser respeitados”: processos disciplinares contra professores paulistas (1887–1896) - Barros, Gabriel Meneses [UNIFESP] (2020)
The last two decades of the 19th century have been agitated throughout the Brazilian territory, especially in São Paulo. With the republican ideology gaining more and more followers, the political reforms that are taking place indicate the rationalization of bureaucratic structures. In this society, an educated people is necessary, so that they vote and respect the laws; thus, education gains a relevance that it had not had until then by the leaders, since it becomes an angular piece in the formation of the citizen. For this reason, the teaching role is of great importance in the civilizing process, and in the irradiation of lights for the population; it is for this reason that there is an increase in the control and disciplinary processes of this professional, so that he/she would follow the legal presuppositions, as a mark of the strategy of the agents for their conduct. However, any pressure exerted generates reactions and conduct outside the norm, which causes the application of disciplinary processes. This dissertation intends to study three forms of disciplinary processes against teachers from São Paulo at the turn of the Empire to the Republic, in the years 1887 ― the year in which the new Regulation for Public Instruction in São Paulo was promulgated ― in 1896 ― the year of the new reform of the São Paulo public instruction, reducing the number of district inspectors. There are three possible occurrences of processes analyzed: against teachers who are absent from their duties; against those who disrespect the superior; and against those who inculcate values contrary to morals and good habits in students. The proposal is to clarify the changes in the laws regarding the processes ― their nuances, modifications and alterations ― and which tactics the teachers use in their defenses ― which arguments and resources are used. The disciplinary proceedings were collected at the Public Archives of the State of São Paulo (APESP) and additional information on the proceedings was found in newspapers of the time, such as the Correio Paulistano and A Província/O Estado de São Paulo. As conclusions, it is clear how the defense movements of teachers have distinctions in cases against men and against women; how disciplinary processes collaborate in the constitution of controlled teachers. The processes also reveal disputes that took place within the Public Instruction.